An open-label, phase IV randomised controlled trial of two schedules of a four-component meningococcal B vaccine in UK preterm infants - Calvert, A; Andrews, N; Barlow, S; Borrow, R; Black, C; Bromage, B; Carr, J; Clarke, P; Collinson, AC; Few, K; Hayward, N; Jones, CE; et al. (BMJ Publishing Group, 2024)
Objective: To compare immunological responses of preterm infants to a four-component meningococcal B vaccine (4CMenB; Bexsero) following a 2+1 vs a 3+1 schedule, and to describe reactogenicity of routine vaccines. Design: An open-label, phase IV randomised study conducted across six UK sites. Setting: Neonatal units, postnatal wards, community recruitment following discharge. Participants: 129 preterm infants born at a gestation of <35 weeks (64 in group 1 (2+1), 65 in group 2 (3+1)) were included in the analysis. Analysis was completed for postprimary samples from 125 participants (59 in group 1, 66 in group 2) and for postbooster samples from 118 participants (59 in both groups). Interventions: Infants randomised to 4CMenB according to a 2+1 or a 3+1 schedule, alongside routine vaccines. Main outcome measures: Serum bactericidal antibody (SBA) assays performed at 5, 12 and 13 months of age: geometric mean titres (GMTs) and proportions of infants achieving titres ≥4 compared between groups. Results: There were no significant differences in SBA GMTs between infants receiving a 2+1 compared with a 3+1 schedule following primary or booster vaccination, but a significantly higher proportion of infants had an SBA titre ≥4 against strain NZ98/254 (porin A) at 1 month after primary vaccination using a 3+1 compared with a 2+1 schedule (3+1: 87% (95% CI 76 to 94%), 2+1: 70% (95% CI 56 to 81%), p=0.03). At 12 weeks of age those in the 3+1 group, who received a dose of 4CMenB, had significantly more episodes of fever >38.0°C than those in the 2+1 group who did not (group 2+1: 2% (n=1); 3+1: 14% (n=9); p=0.02). Conclusions: Both schedules were immunogenic in preterm infants, although a lower response against strain NZ98/254 was seen in the 2+1 schedule; ongoing disease surveillance is important in understanding the clinical significance of this difference. Trial registration number: NCT03125616.